Growth-promoting rhizobacteria improve physiological variables in lemon balm, Melissa officinalis L., subjected to water stress - Ruiz-Berrio, Hernán David; Martínez-Osorio, John Wilson; Alvarado-Sanabria, Óscar Humberto (Revista de Ciencias Agrícolas, 2024)
Climate change has caused droughts in regions that previously did not have water issues, affecting the production of medicinal plants grown in small-scale agricultural units. Plants such as lemon balm, Melissa officinalis L., are sensitive to water stress, which reduces their yield. One alternative to mitigate water stress is the use of plant growth-promoting rhizobacteria (PGPR). However, in the high tropics of Colombia, the use of these microorganisms is not common due to a lack of knowledge about how they can improve water absorption and increase the yield of medicinal plants. This study aimed to determine the effect of native PGPR on lemon balm plants subjected to water stress conditions using a completely randomized design with six treatments and four replications. Applications of Bacillus cereus and Bacillus amyloliquefaciens were made, and the plants were subjected to two water levels (field capacity and 50% field capacity). Physiological variables of stomatal conductance, chlorophyll content, and fluorescence were measured at the end of the experiment. Bacillus cereus significantly improved growth parameters such as number of leaves (115.00±34.71), fresh weight of root (5.51±3.07 g) and shoot (8.32±4.27), Bacillus amyloliquefaciens increased stomatal conductance (401.3 μmol H2O m2 s1) in water-stressed plants. These results suggest that the use of native PGPR considerably improves the growth and development parameters of lemon balm plants and provides a viable alternative for farmers to enhance yield and resistance to water stress conditions.